Rapid-Cycle PCR Method To Detect Bordetella pertussis That Fulfills All Consensus Recommendations for Use of PCR in Diagnosis of Pertussis - Farrell, D. J. (American Society for Microbiology, 2000)
No standardized PCR method is available for the laboratory diagnosis of the pertussis syndrome. Consensus recommendations for the use of PCR in the diagnosis of Bordetella pertussis infections have been proposed, and the aim of this study was to develop a method that fulfills all of these criteria. A rapid-cycle shared-primer PCR method with a microwell format and probe hybridization detection step (POR) was developed using novel oligonucleotides targeted to the outer membrane porin gene (Bordetella spp.). In specimens positive for Bordetella spp., B. pertussis was differentiated from Bordetella parapertussis and Bordetella bronchiseptica by hybridization with organism-specific oligonucleotide probes. An internal control was developed using overlap extension PCR and mouse β-actin DNA. The analytical specificity was 100%. The analytical sensitivity was comparable to that of nested IS481 and IS1001 PCR (∼1 organism per reaction). The clinical sensitivity and specificity were ascertained using 705 specimens (from 705 patients). The results were compared to those of a nested-PCR method targeting the insertion sequences IS481 and IS1001. Fifty-one specimens were positive for B. pertussis by POR and IS481 PCR. Two specimens which fulfilled a clinical definition of pertussis were positive by POR and negative by IS481 PCR. A total of 652 specimens were negative by both methods. B. parapertussis was not detected in any specimens. PCR inhibition was detected in 21 out of 705 specimens (2.98%). Thus, a rapid (4 h, including specimen preparation) PCR method which fulfills all of the consensus recommendations was developed and validated for the detection of B. pertussis.